An Analysis of Acceleration, Deceleration and High-Intensity Skating during Elite Bandy Match-Play: A Case Study - Malin Johansson; Per-Erik Ervasti; Sven Blomqvist (MDPI AG, 2021)
Profiles of physical workload in sports are useful to optimize performance and reduce the risk of injury. The aim of the study was to investigate physical workload in 10 elite bandy players by describing acceleration, deceleration, and high-intensity skating during bandy match-play. During 13 home matches, 10 male elite bandy players wore a GPS unit to measure changes in the total distance, total distance skating in two speed zones, and total distance of acceleration and deceleration. A within-subject design was used to measure changes over time during match-play by comparing first and second halves as well as comparisons for consecutive 15 min intervals. No significant differences were observed for high-intensity or very high-intensity acceleration and deceleration for comparisons by halves or for 15-min intervals. For comparisons by halves, a significant time-dependent effect was observed on very fast skating (1337.6 m vs. 1160.9 m), sprint skating (300.0 m vs. 272.0 m), low-intensity acceleration (342.7 m vs. 333.0 m), and total distance covered (10,916.9 m vs. 10,450.3 m). These variables, along with low-intensity deceleration, were also significant for the 15 min interval comparisons. The results show that there is no time-dependent reduction in high-intensity acceleration and deceleration in elite bandy match-play. However, elite bandy players do not maintain the distance of high-intensity skating throughout a whole match.